The Analysis of Factors Affecting Tax Compliance Among MSMEs In Batam City - Shelvira; Mortigor Afrizal Purba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The primary objective of this study is to assess the impact of the modernization of the tax administration system, tax socialization, and tax supervision on the compliance of micro, small, and medium enterprises (MSMEs) in Batam City. This research adopts a quantitative approach and focuses on the population of MSMEs actors who submitted tax returns to KPP Pratama Batam Selatan in 2022, with total of 2.797 individuals. By applying the Slovin formula with a 10% margin of error, a sample of 100 respondents was selected for the study. The research employs secondary data obtained from books, articles and also directly obtained from KPP Pratama Batam Selatan and primary data collection through the distribution of questionnaires using Google Forms, and the responses will be analyzed utilizing the SPSS version 25 software. The findings indicate a positive and significant correlation between the variables of modernization of the tax administration system, tax socialization, and tax supervision on the tax compliance of MSMEs in Batam City.